2018
DOI: 10.1038/s41467-018-07545-8
|View full text |Cite
|
Sign up to set email alerts
|

Control of Treg cell homeostasis and immune equilibrium by Lkb1 in dendritic cells

Abstract: To balance immunity and tolerance, the endogenous pool of Foxp3+ regulatory T (Treg) cells is tightly controlled, but the underlying mechanisms of this control remain poorly understood. Here we show that the number of Treg cells is negatively regulated by the kinase Lkb1 in dendritic cells (DCs). Conditional knockout of the Lkb1 gene in DCs leads to excessive Treg cell expansion in multiple organs and dampens antigen-specific T cell immunity. Lkb1-deficient DCs are capable of enhancing, compared with wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 55 publications
4
42
2
Order By: Relevance
“…Some evidence suggests that the ligation of surface PD-L1 triggers IL-10 production, which consequently polarizes naive T cells into T reg cells (Kuipers et al 2006 ). However, another study identified Lkb1 as a regulatory switch in DCs for controlling T reg homeostasis, the immune response and tolerance, and the number of T reg cells was negatively regulated by the kinase Lkb1 in DCs (Chen et al 2018 ). Therefore, the signalling pathway initiated by PF-treated DCs to promote Foxp3 + T reg differentiation remains to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that the ligation of surface PD-L1 triggers IL-10 production, which consequently polarizes naive T cells into T reg cells (Kuipers et al 2006 ). However, another study identified Lkb1 as a regulatory switch in DCs for controlling T reg homeostasis, the immune response and tolerance, and the number of T reg cells was negatively regulated by the kinase Lkb1 in DCs (Chen et al 2018 ). Therefore, the signalling pathway initiated by PF-treated DCs to promote Foxp3 + T reg differentiation remains to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Liver kinase B1 (LKB1) programmes the metabolic and functional fitness of Tregs in the control of immune tolerance and homeostasis and functions as a critical inhibitor of DCs immunogenicity, and when lost, mitochondrial fitness is reduced and maturation, migration, and T cell priming of peripheral DCs are increased. Loss of LKB1 specifically primes thymic CD11b + DCs to facilitate thymic Tregs development and expansion, which is independent from AMPK signalling but dependent on mTOR and enhanced phospholipase C β1-driven CD86 expression [ 90 , 91 ]. The specific deletion of LKB1 in Tregs can induce a fatal inflammatory disease characterized by excessive Th2-type-dominant responses, which not only disrupts the survival, mitochondrial fitness and metabolism of Tregs but also induces aberrant expression of immune regulatory molecules, including PD-1 and the TNF receptor superfamily proteins GITR and OX40.…”
Section: New Function and Regulatory Mechanisms For Tregsmentioning
confidence: 99%
“…Therefore, Lkb1 Frontiers in Immunology | www.frontiersin.org may constitute an important factor that DCs use to regulate the immune response. Chen et al note that the above study calls into question the concept of regulatory DCs; it proves the coexecution of regulatory and inflammatory programs controlled by various signals in the same DC as it is activated and matures (109). More research is necessary to study the mechanisms of controlling Lkb1 expression in DCs, as well as the possible association of changes in the activity of this kinase in various DC types when exposed to different autoimmune diseases or tumors.…”
Section: Treg Homeostasismentioning
confidence: 99%